Multiparticulate Systems in the Treatment of Inflammatory Bowel Disease - Lamprecht, A. (Current Drug Targets - Inflammation & Allergy, 2003)
This article shall give an overview on drug delivery systems under development for new therapeutic strategies in the treatment of inflammatory bowel disease. Local delivery of drugs in the colon is mainly aimed to improve efficacy to sideeffect profiles. The various features of the different approaches allowing drug delivery to the inflamed colon are discussed including the main physiological and pathophysiological problems for different systems. Developments for colonic delivery by oral administration always tried to adapt the carriers to the physiological requirements which shall further increase the therapeutic efficiency and improve patient compliance. The newer carriers described here shall allow to exclude certain variations by physiological factors like local pH, transit throughout the gastrointestinal tract, the potential role of gut microflora, and drug dissolution in the diseased large intestine, which always have been impeding conventional carrier systems for this treatment. Therefore, especially new strategies for such treatment will be presented including liposomal formulations, nanoparticles, bacterial cytokine expression and viral gene therapy approaches. Effective and selective delivery even of an otherwise non-specifically acting drug could provide new therapeutic pathways in the treatment of inflammatory bowel disease.
Keywords: nanoparticles